AN ANALYSIS OF THE WANDERING EARTH II BASED ON PIERCE SEMIOTICS - Tang, Zezong; Zhang, Yi (Economics and Statistics Research Journal (ESRJ), 2023)
As a highly-anticipated domestic science fiction series, “The Wandering Earth II” has captured widespread attention and ignited online discussion upon its release. The film weaves together multiple narrative threads, crafting a diverse array of characters and seamlessly blending surreal themes with realist storytelling. Consequently, its content and scope align closely with Peirce’s semiotic framework. As a founding figure in semiotics, Peirce incorporates various societal factors beyond symbols into his semiotic system, endowing it with extensive interdisciplinary applicability and research potential. Hence, this analysis of “The Wandering Earth II” employs Peirce’s semiotic framework to unravel the construction of the film’s symbolic system, with the aim of seeking novel textual expressions for film semiotics research while providing fresh semiotic perspectives on the interpretation of the movie